(3fOje GdcQGe hfSje GdZQGe aj PcQ GdNdaGA GdYXGes - (3eMeO Hf aVGFd Hf YHO GdSGJQ GdMSGejs
(3ChdgG (B:s
(3hHYO aEf Gdehdi GdeGdc CHG efUhQ GdESagSdGQ deG JeMU fXQg HGdQVG Edqi , Chba Lejd GYJbGOg Ydqi s
(3BNQgG (B:s
(3EPG cGfJ dc Edi QLd MGLI, adG JMedfG ef dg bHd ef JSdg EjGgG WYeg Ke CeQ HbVGA MGLJi s
(3gfGc Tc aj Cf eDda GdeNWhW gh fGSNgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B445 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs